Prospective significance of the placenta accreta index and pregnancy outcomes in pregnant women with placenta previa at Hue Central Hospital - Thang, Tran Minh; Tan, Dang Van; Trinh, Le Thi Loan; Quang, Nguyen Van; Anh, Nguyen Thi Kim; Xuan, Nguyen Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Objectives: This study aims to explore the predictive value of placenta accreta scoring system (PASS) in diagnosing placenta accreta spectrum and the birth outcomes in pregnant women with placenta previa at Obstetrics Department of Hue Central Hospital. Method: A cross-sectional descriptive study was conducted on 42 pregnant women who were diagnosed with placenta previa at Obstetrics Department of Hue Central Hospital from January 2021 to December 2021. On ultrasound, PASS was used to assess the potential of placenta accreta spectrum. Results: Pregnant women with placenta previa had at least 1 previous cesarean section accounted for 66.7%. The high-risk group of placenta accreta (PASS ≥ 8 points) was 89 times more likely to predict placenta accreta than the group low-risk and mediumrisk group (< 8 points) (OR= 89.2; 95%CI: 11.4-901.4; p<0.001). The area under the ROC curve (AUC) of the PASS showed a very- high level (AUC: 0.977; p<0.001) to predict the placenta accreta spectrum. The optimal cut-off point was 8 points with a sensitivity of 89.5% and specificity of 91.3%. The PASS was relevant to the hysterectomy, and blood transfusion happened in operation (p<0.001). The proportion of pregnant women with placenta accreta was 45.2%, underwent hysterectomy was 33.3%, needed blood transfusion accounted for 52.4% and had complications during surgery was 23.8%. Gestational age at birth in the group ≥ 38 weeks accounted for the majority, with 69.0%. Newborns weighing 2500 - 3500 grams accounted for 73.8% in the majority. The first minute Apgar > 7 points is 69%, the 5th minute Apgar > 7 points is 95.2%. Conclusion: PASS is strongly recommended to use in predicting of placenta accreta spectrum in pregnant women with placenta previa. PASS is easily and widely applied in clinical practice, suitable for the current situation of almost obstetricians and ultrasound practitioners that are occupied on clinical systems.